Vein patch angioplasty with non-penetrating titanium clips. Comparison to standard suture technique. - Pikoulis, E; Rhee, P; Nishibe, T; Koronarchis, D; Leppäniemi, A; Karavokyros, I; Burris, D; Bakoyiannis, C; Fishback, N; Wherry, D; Rich, N (Acta Chir Belg, 2009)
Our purpose was to compare the Vascular Closure Staples (VCS) clips to a standard suture technique for vein patch angioplasty in a porcine model. Six female pigs underwent vein patch angioplasty of the common iliac arteries with either VCS clips or continuous suturing. The reconstructed vessels were evaluated macroscopically, angiographically and histologically after two months by re-operation. There was a non significant trend towards shorter reconstruction (6.5 +/- 1.8 min. for clips vs. 8.5 +/- 1.7 min. for sutures, p = 0.15) and clamp times when clips were used (8.4 +/- 1.5 min. vs. 10.1 +/- 1.3 min., p = 0.15). At re-operation all vessels were found patent without significant histological differences regarding the intimal reaction. VCS clips are a reliable alternative to sutures for vein patch angioplasty.
Keywords: Anastomosis, Surgical; Angioplasty; Animals; Female; Reoperation; Suture Techniques; Swine; Titanium; Vascular Patency; Wound Healing